Counter-Attack Pasca Penghitungan Suara Pilpres 2019 Menuju Real Count - Ida Susilowati (ADALAH, 2019)
Abstract:The 2019 Presidential General Election is a continuation of the political battle between the two camps, namely the Prabowo camp and the Joko Widodo camp. The two camps have the same strong support, both from the people as voters, as well as the support of political parties participating in the election. After the vote on April 17, 2019, each party claimed to have won the election. Jokowi's camp showed his victory with the results of the Quick Count, while Prabowo's camp showed its victory with the results of their own real count. This debate does not end if the General Election Commission does not immediately announce the results of the general election.Keywords: Presidential Election, Counter Attack, Real Count. Abstrak:Pemilihan Umum Presiden 2019 merupakan kelanjutan pertarungan politik antara dua kubu yaitu kubu Prabowo dan kubu Joko Widodo. Kedua kubu memiliki dukungan yang sama-sama kuat, baik dukungan dari rakyat sebagai pemilik suara, maupun dukungan partai politik peserta pemilu. Pasca pemungutan suara tanggal 17 Agustus, masing-masing pihak mengklaim telah memenangkan pemilu. Kubu Jokowi menunjukkan kemenangannya dengan perolehan hasil dari Quick Count, sedang kubu Prabowo menunjukkan kemenangannya dengan hasil real count yang mereka lakukan sendiri. Perdebatan ini tidak berujung bila Komisi Pemilihan Umum tidak segera mengumumkan hasil pemilihan umum.Kata Kunci: Pemilihan Umum Presiden, Counter  Attack, Real Count.